Morphology of the Roots and Canals of Mandibular Third Molars, Their Symmetry and Related Factors Using Cone-Beam Computed Tomography - Hafezi, Ladan; Sakhdari, Shirin; Moaiyedmohseni, Negin (Iranian Endodontic Journal, 2019)
Introduction: Adequate knowledge about the anatomy of the roots and canals of mandibular third molars is imperative for a successful treatment. This study aimed to use cone-beam computed tomography (CBCT) to evaluate the morphology of the roots and canals of mandibular third molars and their symmetry. Methods and Materials: Totally, 110 CBCT images of bilateral mandibular third molars were evaluated in terms of the number of roots and canals, canal type, isthmus location, location of accessory canals, degree of root curvature and its direction, age and sex of patients and the symmetry of variables in the right and left sides of the mandible. The descriptive statistics, t-test and chi-square test were applied to analyze data. Results: Of all, 71.36% of mandibular third molars had two roots, 20.9% had one single root and 7.72% had three roots. The distal root had one single canal in 89.08%. The mesial root had one single canal in 44.25% and two canals in 49.42%. The Vertucci’s types I (45.40%) and IV (34.48%) had the highest frequency in the mesial root while type I (91.95%) had the highest frequency in the distal root. The deviation of mesial root was towards the distal while distal roots were mainly straight. Conclusion: The symmetry between the right and left mandibular third molars was significantly high. In case of encountering anatomical complexities in dental treatment of a mandibular third molar, dental clinicians should consider the high possibility of presence of the same condition in the contralateral mandibular third molar. Keywords: Anatomy; Cone-Beam Computed Tomography; Mandible; Third Molar